Flora fóssil dos níveis de bentonita da formação Campos Novos (Oligoceno Superior) Bacia de Boa Vista, PB, Brasil - Paniz, Guilherme Artur (Universidade do Vale do Rio dos Sinos, 2015)
The end of Oligocene was a critical time for angiosperm evolution, with the definitive establishment of modern vegetation and grass-dominated landscapes. Is was also a time marked by important geological events, with the first signs of the Andean uplift that led to closure of the Central America seaways and the resulting phytogeographic results. In the present article a new association of fossil plant imprints is described from a bentonitic shale interval of the Campos Novos Formation, for which 40Ar/39Ar geochronological dating has indicated a Late Oligocene age. This unit is part of the depositional sequence of the Boa Vista Basin, a small pull-apart basin in northeastern Brazil, established over a Pre-Cambrian basement and affected by tectonic and magmatic impacts. This taphoflora consists exclusively of angiosperm morphotypes, which are represented by leaves, leaflets, legume fruits (with a new genus Albisiocarpum proposed), a fragmentary flower, and one specimen from a probable monocot. Among these taxa, the Fabaceae-related forms stand out for their abundance (48% of representativeness), followed by Lauraceae (with a new species, Nectandra bonavistensis), Annonaceae, Burseraceae, Anacardiaceae, Myrtaceae, and Malvaceae. The dominant microphyllic leaves, with entire margins and brochidodromous venation, support the presence of a warm tropical climate, yet with times of more stressing conditions (seasonal or with hydric restriction). Comparisons made with other Cenozoic floral assemblages from Brazil and neighboring areas suggest the closest relations with Middle Eocene-Oligocene deposits from central and SE Brazil, and with assemblages preserved in Late Oligocene deposits from northern Brazil and the Caribbean region. This suggests a retraction of the tropical floras from higher to lower latitudes throughout the Oligocene, also probably linked to the short interval of climatic amelioration that occurred at the end of the period. Modern analogs show a mixed flora of Amazonian, Cerrado, and Atlantic Forest components, or an ecotone, with most of these displaying pioneer behavior. This fóssil flora from the Boa Vista basin shows the potential for building a well-dated record for the fóssil floras that precede the end of the Paleogene in Brazil.
Keywords: Flora fóssil; Angiospermas; Plantas tropicais; Bentonita; Campos Novos; Bacia de Boa Vista; Fossil flora; Angiosperms; Tropical plants; Bentonite; Boa Vista Basin; ACCNPQ::Ciências Exatas e da Terra::Geologia